Impact of annealing temperature to the performance of hematite based humidity sensor - W.R.W. Ahmad; M.H. Mamat; Z. Khusaimi; A.S. Ismail; M. Rusop (Institute of Advanced Engineering and Science, 2019)
In the present study, hematite (α-Fe2O3) nanorod structure were grown on fluorine doped tin oxide coated glass substrate via sonicated immersion approach with variation of annealing temperature (350˚C – 600˚C) in one-hour treatment. The impact of varying the temperature of annealing treatment on crystalline phase, structure morphology, optical properties and humidity sensing performance of hematite were examined. X-ray diffraction pattern disclosed a rhombohedral structure with α-phase diffraction peaks. The surface morphology images taken from field emission scanning electron microscopy revealed that the hematite nanorod arrays were grown uniformly in all samples and the average diameters of nanorods were measured in the ranges between 55 and 80 nm. Ultraviolet–visible spectroscopy measurement spectra show that all samples exhibited good optical properties. The hematite humidity sensor sample annealed at 400°C has demonstrated the highest sensitivity response (S=177.78) to humidity range between 40%RH to 90%RH.